Beyond "see one, do one, teach one": toward a different training paradigm. Issue 1 (9th February 2009) - Rodriguez-Paz, J M; Kennedy, M; Salas, E; Wu, A W; Sexton, J B; Hunt, E A; Pronovost, P J
Abstract : In the process of acquiring new skills, physicians-in-training may expose patients to harm because they lack the required experience, knowledge and technical skills. Yet, most teaching hospitals use inexperienced residents to care for high-acuity patients in complex and dynamic environments and provide limited supervision from experienced clinicians. Multiple efforts in the last few years have started to address the problem of patient safety. Examples include voluntary incident-reporting systems and team training workshops for practising clinicians. Fewer efforts have addressed the deficits in training new physicians, especially related to knowledge, skills and competence. The current apprenticeship or "see one, do one, teach one" model is insufficient because trainees learn by practising on real patients, which is particularly an issue when performing procedures. Residents have expressed that they do not feel adequately trained to perform procedures safely by themselves. In this paper, we conduct an informal review of the impact of current training methods on patient safety. In addition, we propose a new training paradigm that integrates competency-based knowledge and clinical skills, with deliberate attitudinal and behavioural changes focused on patient safety in a safe medically simulated environment. We do so with the hope of creating a better marriage between the missions of training and patient safety.